Neurological consultations and diagnoses in a large, dedicated COVID-19 university hospital - Adalberto STUDART-NETO; Bruno Fukelmann GUEDES; Raphael de Luca e TUMA; Antonio Edvan CAMELO FILHO; Gabriel Taricani KUBOTA; Bruno Diógenes IEPSEN; Gabriela Pantaleão MOREIRA; Júlia Chartouni RODRIGUES; Maíra Medeiros Honorato FERRARI; Rafael Bernhart CARRA; Raphael Ribeiro SPERA; Mariana Hiromi Manoel OKU; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: More than one-third of COVID-19 patients present neurological symptoms ranging from anosmia to stroke and encephalopathy. Furthermore, pre-existing neurological conditions may require special treatment and may be associated with worse outcomes. Notwithstanding, the role of neurologists in COVID-19 is probably underrecognized. Objective: The aim of this study was to report the reasons for requesting neurological consultations by internists and intensivists in a COVID-19-dedicated hospital. Methods: This retrospective study was carried out at Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, Brazil, a 900-bed COVID-19 dedicated center (including 300 intensive care unit beds). COVID-19 diagnosis was confirmed by SARS-CoV-2-RT-PCR in nasal swabs. All inpatient neurology consultations between March 23rd and May 23rd, 2020 were analyzed. Neurologists performed the neurological exam, assessed all available data to diagnose the neurological condition, and requested additional tests deemed necessary. Difficult diagnoses were established in consensus meetings. After diagnosis, neurologists were involved in the treatment. Results: Neurological consultations were requested for 89 out of 1,208 (7.4%) inpatient COVID admissions during that period. Main neurological diagnoses included: encephalopathy (44.4%), stroke (16.7%), previous neurological diseases (9.0%), seizures (9.0%), neuromuscular disorders (5.6%), other acute brain lesions (3.4%), and other mild nonspecific symptoms (11.2%). Conclusions: Most neurological consultations in a COVID-19-dedicated hospital were requested for severe conditions that could have an impact on the outcome. First-line doctors should be able to recognize neurological symptoms; neurologists are important members of the medical team in COVID-19 hospital care.